Assessment of Equipment and Machinery Assets for the Purpose of Disposal in Certain Non-Vertical Work Units of Groundwater Raw Water of the Nusa Tenggara II River Basin Center, Kupang City - Elda Rade Wadoe; Cicilia Apriliana Tungga; Maria Indriani Hewe Tiwu; Aldarine Molidya (Sean Institute, 2026)
This study aims to determine the fair value of equipment and machinery assets at the Specific Non-Vertical Groundwater Raw Water Work Unit (SATKER ATAB) of the Nusa Tenggara II River Basin Center in Kupang City as a basis for the asset write-off process. This study uses a quantitative descriptive approach with a case study design. Primary data were obtained through interviews and observations of the physical condition of the assets, while secondary data were obtained from inventory documents and financial reports. The sample consisted of seven units of heavy equipment including truck cranes, compressors, and earth drilling machines. Two valuation methods were used, namely the cost approach and the market approach in accordance with the 2022 Indonesian Valuation Standards (SPI) and PMK No. 111 / PMK.06 / 2016. The results showed that the fair value of severely damaged assets based on the cost approach was IDR 74,993,000 with a liquidation value of IDR 59,994,400. Meanwhile, the market approach resulted in a total value of IDR 163,307,352 with a liquidation value of IDR 130,645,881. The study concluded that the cost approach is more appropriate for scrap assets, while the market approach is more representative for assets that still have potential resale value. The results of this assessment can be used as a basis for setting auction limits and supporting an accountable asset disposal process.